2004
DOI: 10.1213/01.ane.0000121771.78755.f4
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Promotes Endothelium-Dependent Smooth Muscle Relaxation in Isolated Human Omental Arteries and Veins

Abstract: Anesthesia with sevoflurane is accompanied by vasodilatation. This could be due to the effects of sevoflurane on endothelium-dependent relaxation. We measured muscle tension of isolated human omental arteries and veins in response to substance P or glyceryl trinitrate in the presence of sevoflurane (0%, 1%, 2%, or 4%). Vascular levels of guanosine 3', 5'-cyclic monophosphate were measured with enzyme-linked immunosorbent assay. Substance P induced an endothelium- and concentration-dependent relaxation in oment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…108 Such intervention is not always needed because of the activation of sympathetic and renin-angiotensin systems; this is associated with an increase of MCFP and maintenance of the needed MCFP-CVP gradient to preserve VR and CO. 103,109,110 Anesthetics, sedatives, and other interventions might minimize such a homeostatic response. 105,[111][112][113][114] Positions (Tilts) Different positions, e.g., head up versus head down, affect systemic hemodynamics including function of the venous system. A head-up position (e.g., standing up) could be associated with a gravity-induced shift of blood volume from the upper to the lower part of the body.…”
Section: Fig 4 Two-compartment Model Inside: the Two Circuits Reprmentioning
confidence: 99%
“…108 Such intervention is not always needed because of the activation of sympathetic and renin-angiotensin systems; this is associated with an increase of MCFP and maintenance of the needed MCFP-CVP gradient to preserve VR and CO. 103,109,110 Anesthetics, sedatives, and other interventions might minimize such a homeostatic response. 105,[111][112][113][114] Positions (Tilts) Different positions, e.g., head up versus head down, affect systemic hemodynamics including function of the venous system. A head-up position (e.g., standing up) could be associated with a gravity-induced shift of blood volume from the upper to the lower part of the body.…”
Section: Fig 4 Two-compartment Model Inside: the Two Circuits Reprmentioning
confidence: 99%
“…The number of studies using isolated human vessels 122, 144,146,151,168,183,193,202,223,[302][303][304][305][306][307][308] is increasing, and they have reported both similarities and differences in vascular responsiveness to general anesthetics between humans and animals. However, as discussed above, the underlying mechanisms are not entirely clear.…”
Section: Investigations With Human Vesselsmentioning
confidence: 99%
“…However, as discussed above, the direct action of volatile anesthetics on arterial VSMCs may contribute to the prolonged systemic hypotension observed during the postanesthesia period. 157,158,294,303,305,307,308,[317][318][319] Again, on consideration of possible species differences, further studies using human capacitance vessels, as well as human systemic resistance vessels, would be essential to evaluate a possibility that the direct (i.e., nonneural) actions of general anesthetics on VSMCs contribute to systemic hypotension during their administration. 2 In previous studies with isolated mesenteric veins, 157,158,317 halothane, enflurane, and isoflurane inhibited the contractile response to norepi- nephrine.…”
Section: Investigations With Systemic Resistance and Capacitance Vesselsmentioning
confidence: 99%
“…However, sevoflurane depresses sympathetic neuromuscular transmissions in human omental vessels by decreasing neuronal norepinephrine release and artery sensitivity, at least at concentrations above 2 vol% (19). In addition, Thorlacius and Bodelsson demonstrated that vasodilating effects of sevoflurane on human arteries were found to be significant only at the 4 vol% of concentration not at 1 vol% and 2 vol% (20).…”
Section: Discussionmentioning
confidence: 99%